DNA Photosensitization by an "Insider": Photophysics and Triplet Energy Transfer of 5‐Methyl‐2‐pyrimidone Deoxyribonucleoside. Issue 32 (1st July 2015) - Bignon, Emmanuelle; Gattuso, Hugo; Morell, Christophe; Dumont, Elise; Monari, Antonio
Abstract The main chromophore of (6‐4) photoproducts, namely, 5‐methyl‐2‐pyrimidone (Pyo), is an artificial noncanonical nucleobase. This chromophore has recently been reported as a potential photosensitizer that induces triplet damage in thymine DNA. In this study, we investigate the spectroscopic properties of the Pyo unit embedded in DNA by means of explicit solvent molecular‐dynamics simulations coupled to time‐dependent DFT and quantum‐mechanics/molecular‐mechanics techniques. Triplet‐state transfer from the Pyo to the thymine unit was monitored in B‐DNA by probing the propensity of this photoactive pyrimidine analogue to induce a Dexter‐type triplet photosensitization and subsequent DNA damage.